Psychosocial and Socio-Economic Crisis in Bangladesh Due to COVID-19 Pandemic: A Perception-Based Assessment - Bodrud-Doza, Md.; Shammi, Mashura; Bahlman, Laura; Islam, Abu Reza Md. Towfiqul; Rahman, Md. Mostafizur (Frontiers in Public Health, 2020)
Background: The spread of COVID-19 pandemic, the lockdown/partial lockdown, the disease intensity, weak governance in the healthcare system, insufficient medical facilities, unawareness, and various misinformation in the mass media led people to fear and anxiety. The present study intended to conduct a perception-based analysis to get the idea of the peoples’ psychosocial, socio-economic crisis, and possible environmental crisis amidst the COVID-19 pandemic in Bangladesh. Methods: A perception-based questionnaire was surveyed online nationwide for Bangladeshi citizens of 18 years and/ or older. The sample size was 1066 respondents. Datasets were analyzed through a set of statistical techniques including principal component analysis (PCA), hierarchical cluster analysis (CA). Results: There was a positive significant association between fear of COVID-19 outbreak with the struggling healthcare system (p<0.05) of the country. Also, the negative association between the fragile health system of Bangladesh and the government’s ability to deal with the pandemic (p<0.05) revealing the poor governance in the healthcare system. Again, a positive association of shutdown and social distancing with the fear of losing own or family members` life, and due to lack of healthcare treatment (p<0.05) reveals that due to the decision of shutting down normal activities were obstructed that may lead to mental and economic stress. However, a positive association of socio-economic impact of the shutdown with poor people’s suffering, the price hike of basic need, hamper of formal education (p<0.05) the possibility of severe socio-economic and health crisis will be aggravated. Moreover, there is a possibility of climate change-induced disaster and infectious diseases like dengue during/after the COVID-19 situation which will create severe food insecurity (p<0.01) and further healthcare crisis. Conclusions: The partial lockdown in Bangladesh due to the COVID-19 pandemic increased community transmission, healthcare crisis, economic burden, loss of GDP despite the resuming of industrial operations. In society, it has created psychosocial and socio-economic insecurity due to the loss of lives and livelihoods. The government should take proper inclusive steps for risk assessment, communications, and financial stimulus towards the public to alleviate their fear and anxiety, and to take proper action to boost mental health and wellbeing.